Evaluation of a Commercial Air Filter for Removal of Virus from the Air - Roelants, P. (1968)
The effectiveness of a commercial absolute air filter for removal of viruses from air was tested with an actinophage, under the usual conditions of a laminar airflow clean room. A new method of dry phage dispersion is described. The filter showed an average reduction of 99.996% of airborne actinophage.